2020
DOI: 10.5114/ada.2018.79567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carotid intima media thickness and hematologic inflammatory markers in patients with chronic spontaneous urticaria

Abstract: Introduction: Low grade inflammation is associated with chronic spontaneous urticaria (CSU) and atherosclerosis. There are little data on the relationship between urticarial inflammation and atherosclerosis. The neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR) and mean platelet volume (MPV) have recently been studied in many diseases as a biomarker of inflammation. Aim: To evaluate hematologic inflammatory parameters and subclinical atherosclerosis in CSU patients. Material and methods: C-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The latest research focuses on the role of CRP in urticaria and metabolic syndrome. Yaldiz and Asil [97] found that CRP levels and HDL levels are negatively correlated, so CU may increase the risk of atherosclerosis [97]. For CSU patients with poor effect of antihistamines, their plasma CRP levels are significantly increased [98], for patients treated with omalizumab, and CRP levels significantly decreased after 12 weeks of treatment and are closely associated to UASs [99].…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…The latest research focuses on the role of CRP in urticaria and metabolic syndrome. Yaldiz and Asil [97] found that CRP levels and HDL levels are negatively correlated, so CU may increase the risk of atherosclerosis [97]. For CSU patients with poor effect of antihistamines, their plasma CRP levels are significantly increased [98], for patients treated with omalizumab, and CRP levels significantly decreased after 12 weeks of treatment and are closely associated to UASs [99].…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…In this study, it might have been discovered that there is no statistically noteworthy Contrast the middle of two concentrated on gatherings as respects good CCA IMT (mm) Also exited CCA IMT (mm). This is as opposed for Yaldiz Furthermore Asil, [10], who discovered that good Also exited CIMT qualities were statistically fundamentally higher in the CSU aggregation Likewise contrasted with the solid control bunch.…”
Section: Discussionmentioning
confidence: 82%
“…42 A long time. This may be in understanding with Yaldiz Also Asil, [10] who led An investigation around cu patients for intend agdistis 37. 7 ± 7.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations